PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL (TARL) UNTUK MENGAKOMODASI PERBEDAAN SES (STATUS SOSIAL EKONOMI) PESERTA DIDIK - Elly Sukmanasa; M. Afifuddin Khotibul Umam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the application of Teaching at the Right Level (TaRL) to overcome academic gaps due to differences in socioeconomic status (SES) at SDN Empang 2, Bogor City. The TaRL approach adapts learning to the ability of students, not based on age or class. The research method uses qualitative descriptive case studies, with data collection techniques through observation, interviews, and document analysis. The subjects of the study were 26 students of class 6A and teachers of SDN Empang 2. The results of the study show that SES affects students' access to learning resources and parental support, thus having an impact on academic achievement. The TaRL approach, which groups students based on ability, has been shown to increase formative evaluation value, especially in students with low ability. In addition to improving academic outcomes, this approach reduces stress and increases students' confidence. With the implementation of TaRL, teachers can reduce academic gaps due to SES differences and create a more inclusive learning environment.